Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1002/food.19860300337
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐polysaccharide complexes as surfactants

Abstract: A study has been made of surface pressure (pi) and maximum shear stress (Ps) (at a constant shear rate) of decane-water interface on which bovine serum albumin (BSA) and its complexes with dextran sulfate (DS) were adsorbed. The pi values have been monitored by the Wilhelmy plate technique. The Ps values have been measured with a surface viscoelastometer. The changes of pi with time for BSA and BSA-DS complexes in general takes place in two stages which can be attributed to two corresponding limiting factors: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Where a protein and highly charged polysaccharide are introduced simultaneously, the formation of an electrostatic complex between the two biopolymers can be expected to affect the steps of diffusion, adsorption, and reorganization to differing extents. For example, the adsorption of bovine serum albumin−dextran sulfate (BSA−DS) complexes at the oil−water interface has been reported to take place in two stages: diffusion and rearrangement of the complexes, with a substantially longer diffusion stage. Ganzevles and co-workers have reported much slower diffusion of β-lactoglobulin−pectin complexes at the air−water interface because of the greater hydrodynamic radius of the complexes compared to the pure protein.…”
Section: Introductionmentioning
confidence: 99%
“…Where a protein and highly charged polysaccharide are introduced simultaneously, the formation of an electrostatic complex between the two biopolymers can be expected to affect the steps of diffusion, adsorption, and reorganization to differing extents. For example, the adsorption of bovine serum albumin−dextran sulfate (BSA−DS) complexes at the oil−water interface has been reported to take place in two stages: diffusion and rearrangement of the complexes, with a substantially longer diffusion stage. Ganzevles and co-workers have reported much slower diffusion of β-lactoglobulin−pectin complexes at the air−water interface because of the greater hydrodynamic radius of the complexes compared to the pure protein.…”
Section: Introductionmentioning
confidence: 99%
“…Burgess () reported that the high viscosity of albumin–gum arabic coacervate was responsible for producing capsules that were fairly stable against coalescence, even in the absence of cross‐linkers. It was shown, as early as 1980s, that the formation of complex coacervate between bovine serum albumin and dextrane sulfate resulted into increased shear strength of films formed at the liquid interface (Gurov & Nuss, ). Thomassin, Merkle, and Gander () also found that the encapsulation process is influenced by the viscoelasticity of the coacervate.…”
Section: Introductionmentioning
confidence: 99%
“…, 1989). Studies on complexes of ovalbumin (Noguchi, 1956), bovine serum albumin (Gurov & Nuss, 1986; Kato et al. , 1989; Dickinson & Galazka, 1992; Izgi & Dickinson, 1995; Dickinson & Pawlowsky, 1996; Galazka & Ledward, 1996) and dextran sulphate revealed that both electrostatic and covalent complexes were formed.…”
Section: Introductionmentioning
confidence: 99%